Principal Management in Improving the Professionalism of Teachers in MA Muhammadiyah Rejang Lebong - Dinar Putri Pratiwi; Deri Wanto (Institut Agama Islam Negeri Sorong, 2022)
The principal is a leader or mentor at the unit level of the school who is responsible for the success and failure of the school he leads. Principals are required to have various competencies, both related to administrative affairs, in order to develop and advance their schools effectively, efficiently, independently, innovatively, and productively. This study aims to describe and examine more deeply how principal management and principal management steps in improving teacher professionalism. For this type of research is qualitative research with a case study design taking data sources on principals and teachers through observation techniques, interviews, and documentary data collection. This data is analyzed then in the form of data analysis, data presentation and conclusion drawing. The results showed that the management of the principal at MA Muhammadiyah Rejang Lebong consisted of planning, implementing, supervising, and organizing. The principal is a leader in an educational institution whose function is as an educator, manager, supervisor, motivator, and innovator. The management steps taken by the principal are to carry out supervision, then the order that always used to support teacher discipline in terms of time, administration to see the learning equipment to be used, and reward teachers who take part in competitions, motivate and encourage continuing education. The supporting factors for the principal's management in improving teacher professionalism can be caused by the fulfillment of funds, teaching staff, sufficient students, discipline, motivation, and a conducive environment, while the inhibiting factor is that there are still many honorary teachers who have not been certified compared to civil servant teachers.